Effects of pre-storage dipping in calcium chloride and salicylic acid on the quality attributes of stored Khalal Barhi dates - Atia, Ahmed; Abdelkarim, Diaeldin; Younis, Mahmoud; Alhamdan, Abdullah (International Journal of Agricultural and Biological Engineering, 2020)
Barhi is a high-quality date cultivar, typically harvested and consumed fresh at the Khalal maturity stage when the fruits are crispy and sweet with bright yellow color. The shelf-life of the Khalal stage (2-3 weeks) is very short for effective marketing. This study aimed at investigating the role of calcium chloride (CaCl2) and salicylic acid (SA) as pre-storage treatments in preserving the color and texture of the fruit during both cold and controlled atmosphere (CA) storage systems. Fresh-harvested Barhi fruits at the Khalal stage were treated with CaCl2 (2%) or SA (2.0 mM), and then stored in cold and CA systems. The weight loss and decay percentages in the treated samples decreased, whereas the total soluble solids of the treated samples increased compared with those of the untreated ones. The best treatment in limiting changes in the color and texture of the fruits was CaCl2 treatment during CA storage.Keywords: Barhi dates, calcium chloride, salicylic acid, color texture, controlled atmosphere storageDOI: 10.25165/j.ijabe.20201303.4983Citation: Atia A, Abdelkarim D, Younis M, Alhamdan A. Effects of pre-storage dipping in calcium chloride and salicylic acid on the quality attributes of stored Khalal Barhi dates. Int J Agric & Biol Eng, 2020; 13(3): 206–212.